Relations between depression and cultural contingencies in modern societies: a behavioral analytic account (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
In Behavior Analysis, depression was defined with reference to a set of relations, produced by ontogenetic and cultural variables. Based on a behavior-analytic account, this article focus on cultural variables that define the features of depression in individualized societies. First, a synthesis of the behavior-analytic approach to depression is presented. Then, depression is considered in the light of complex behavioral phenomena, and conceived in terms of the relations that constitutes each of its occurrences. It is emphasized that the relations determined by cultural variables makes depression a more complex phenomenon, which reflects on the necessity of different therapeutic interventions. At last, some aspects of the individualization process are pointed out, in order to indicate how specific contingencies arrays from modern, individualized societies promoted specific patterns of relationship between the subjects with themselves and with others, which determine the acquisition and maintenance of certain behavioral repertoires classified as depression.
Keywords: depression; behavior analysis; complexity of behavioral phenomena; individualization process